Optimal electric vehicles charging infrastructure planning - Lam, Gibson Jing Sen (Nanyang Technological University, 2021)
As climate change becomes an increasingly pressing issue, governments and international organisations worldwide turn towards environmentally friendly measures and alternatives. Electric vehicles (EV) became one of the most popular solutions and alternatives in replacing conventional internal combustion engine (ICE) vehicles due to their lower greenhouse gas (GHG) emissions and dependency on fossil fuels. However, widespread adoption of EVs is hampered by the lack of infrastructure and the availability of EVs in the market A key reason for people being adverse towards EVs is range anxiety - the fear of the vehicle breaking down due to insufficient battery capacity. Range anxiety is prevalent as the EV market remains in its infancy stage where charging infrastructure is scarce or insufficient for drivers to feel at ease. This report covers the study of planning the optimal locations of EV charging infrastructures and measures to reduce range anxiety in Singapore’s context. As part of the Land Transport Master Plan 2040, Singapore seeks to phase out ICE vehicles and replace them with EVs within the next 20 years. Hence, the need for a meticulously planned EV charging infrastructure is essential and urgent for the meticulous, especially in Singapore where available land is scarce. In this report, the author will discuss an overview of the situation of EVs, EV charging methods and alternatives as well as EV sharing services. Based on the data collected from an online survey conducted for this study, a proposed plan for optimisation of EV charging infrastructure planning is derived that extensively covers multiple aspects and factors for Singapore. At the end of the report, the author will explain the limitations of this study, the feasibility of implementation of the proposed plan and suggested adaptations for the proposed plan to be successful in the long term and overseas.